Mental models impacts on organizational performance: a study in the metal-mechanic sector - Dias, Deise Taiana de Ávila; De Toni, Deonir (Revista de Administração da UFSM, 2020)
The objective of this study was to analyze the impacts of entrepreneurs’ mental models on organizational performance. We identified in the literature that some dimensions form mental models, which are: Knowledge, Emotional Skills, Linear Mind, Relationship, Communication, Strategy, Creativity and Innovation, and Vocation. From quantitative descriptive research, we employed multivariate statistics to analyze the data, using Structural Equation Modeling. By checking the coefficient of determination (R²), we identified that entrepreneurs’ mental models explain 27.1 % of organizational performance. The dimensions that most impacts on organizational performance were: (i) Creativity and Innovation, (ii) Communication, and (iii) Emotional Skills. Among the contributions of this work, we highlight, first, the understanding of how and how much the dimensions influence organizational performance, second, the validation of a scale to measure the entrepreneurs’ mental model dimensions and their impacts on organizational performance.